Quartz OSL dating of palaeosols intercalated with basaltic lava flows and scoria deposits from monogenetic volcanoes in northeastern Jeju Island, Korea - Yeo, Eun-Young; Choi, Jeong-Heon; Ahn, Ung San; Cheong, Albert Chang-sik (Geosciences journal (Seoul, Korea), 2019)
Abstarct Jeju Island, which lies on the continental shelf in the southern Korean Peninsula, is the emergent portion of a basaltic volcanic field that has erupted since the Early Pleistocene (ca. 1.8 Ma). Volcanic activity that continued into historic times (ca. 1 ka) formed an elongated shield with a central edifice (Mt. Halla) and more than 300 monogenetic cones and rings. The establishment of a temporal framework for Jeju volcanism, particularly during the Late Pleistocene and Holocene activities, requires geochronological tools other than radiometric dating techniques, which are based on parent-daughter isotope pairs with geologically long half-lives, such as 40 Ar/ 39 Ar dating. In this study, we conducted quartz optically stimulated luminescence (OSL) dating of palaeosols intercalated with basaltic lava flows and scoria deposits, presumably ejected from three monogenetic volcanoes (Cheoreum, Darangsh and Dunjibong volcanoes) in the northeastern part of the island. Quartz extracts from the palaeosols had moderate to dim sensitivity to optical stimulation, but several prerequisite tests of the measurement protocols for equivalent dose estimation were successful. The coarse (63–250 μm) and fine (4–11 μm) quartz fractions yielded continuous wave (CW)-OSL ages of 19.9–7.0 and 18.6–6.7 ka, respectively, both of which were broadly consistent with the radiocarbon dates (10245–7440 Cal yr BP). These ages indicate that lava flows and scoria deposits covering the palaeosols are younger than ~7 ka. The pulsed OSL signals in coarse quartz extracts from the palaeosols suffered from poor counting statistics, thus it is recommended that they not be applied solely (i.e., without any other absolute ages to compare) to dating dim samples. From one of the sites investigated here, the averaged sedimentation rate of the palaeosol is estimated to be ~0.05 mm/yr, based on stratigraphically consistent CW-OSL ages. The OSL ages presented in this paper, together with previous OSL and radiocarbon ages, confirm that Jeju volcanic island was regionally active during the Holocene.